Analisis Kepuasan Generasi Z Terhadap Layanan E-Commerce - Erwin Permana; Dela Setia Cahyani; Famita Wijayanti; Syamsurizal Syamsurizal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Generation Z is a generation that was born and developed along with the development of digital technology. Generation Z has unique preferences in online shopping with a tendency to choose convenience and affordability. This creates challenges and opportunities for e-commerce players. This research aims to analyze Generation Z's satisfaction with e-commerce services. The research was conducted using a qualitative descriptive approach. Data comes from search results on various digital bases and related official publications. The research results show that Generation Z pays attention to affordable prices as well as high ease of access, product quality, lots of discounts, varied payment method choices, guarantees and speed of delivery. Apart from that, satisfaction with service for a product for Generation Z from e-commerce is obtained because of the efficiency and practicality when shopping offered by e-commerce. With all the convenience provided, as well as efficiency and time effectiveness, e-commerce is considered the right solution in finding needs for Generation Z. Therefore, it is not surprising that more and more platforms are emerging that are used to facilitate the purchase and sale of products or services via the internet. This e-commerce trend has also caused several shops to lose competition and close. This shows that e-commerce is an option for Generation Z, and they are satisfied with the service and convenience provided.